External Validation of CHOKAI and STONE Scores for Detecting Ureter Stones in the Eastern Turkish Population - Fesih Ok; Emrullah Durmuş (Journal of Urological Surgery)

(untitled)
Objective:To investigate the effectiveness of CHOKAI and STONE scoring systems in predicting ureter stones in patients admitted to emergency and urology departments.Materials and Methods:This was a single-center prospective observational study. Patients over the age of 18 years with back, flank, or lower abdominal pain and suspected of ureteral stones and performed non-contrast abdominal computed tomography for diagnostic imaging were included. Each patient’s CHOKAI and STONE score was calculated on their medical interviews and physical and laboratory findings. Receiver operating characteristic analysis was used for the sensitivity and specificity of the scoring systems at optimal cut-off values.Results:Of the 348 patients in the study, 228 were detected with ureteral stones. For the CHOKAI score, the area under the curve (AUC) at an optimal cut-off point of 8 was 0.923 [95% confidence interval (CI), 0.894-0.952], with a sensitivity of 0.842, and specificity of 0.975, a positive likelihood ratio (LR+) of 33.68, and a negative likelihood ratio (LR-) 0.162. For the STONE score, the AUC at an optimal cut-off point of 9 was 0.847 (95% CI, 0.807-0.887), with a sensitivity of 0.697 and specificity of 0.900, an LR+ of 6.97, and an LR- 0.336.Conclusion:The CHOKAI score is more sensitive and specific than the STONE score in predicting ureteral stones. Using the CHOKAI score in routine practice will reduce radiation exposure and cost and prevent time loss for serious differential diagnosis.